IMPLEMENTASI LITERASI NUMERASI DALAM PEMBELAJARAN MATEMATIKA KELAS V SEKOLAH DASAR - Maharani, Dina; Anggraeni Siwi, Dwi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to: 1) describe the implementation of numeracy literacy in mathematics learning for fifth graders of elementary school; 2) describe the impact of the implementation of numeracy literacy on the mathematics learning process for fifth graders of Mertan 03 State Elementary School, Bendosari District, Sukoharjo Regency. This study uses a qualitative approach with descriptive methods. The subjects of the study were homeroom teachers and fifth graders of Mertan 03 State Elementary School. Data collection was carried out through observation, interviews, and documentation, then analyzed through data reduction, data presentation, and drawing conclusions, and tested for validity using triangulation of sources and techniques. The results of the study indicate that: (1) The implementation of numeracy literacy in mathematics learning for fifth graders of Mertan 03 State Elementary School has been carried out systematically through three stages, namely planning, implementation, and evaluation. In the planning stage, teachers developed Project Based Learning (PjBL) based teaching modules that integrate real-life contexts with contextual LKPD and concrete media. In the implementation stage, learning was designed interactively through data collection, table and bar chart analysis, solving story problems, group discussions, and presentations. At the evaluation stage, assessment is carried out holistically based on a process that includes students' attitudes, activeness, and thinking skills. (2) The implementation of numeracy literacy has a positive impact on the mathematics learning process, which can be seen in the increase in student participation and activeness, the development of the ability to read and interpret data, the increase in mathematical communication skills, and the growth of students' awareness of the relevance of mathematics in everyday life.